Prevalence of depression and anxiety in chronic kidney disease patients - Osama Habib, Fahmina Ashaq, Nauman Ismat Butt, Hafiz Hamad Ashraf, Khalid Mahmood, Aniqa Anser, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Previous research on the prevalence of depression and anxiety disorders in patients with chronic kidney disease (CKD) has shown a high prevalence of both types of disorders. The aims of this study was to assess the prevalence of depression in anxiety disorders in CKD patients admitted at a tertiary care facility in Lahore, Pakistan. Materials and methods: All admitted patients at one of the medical wards at Jinnah hospital Lahore from December 2018 to December 2019 with a diagnosis of CKD were invited to participate in this study. Aga khan university anxiety and depression scale was used to assess the prevalence of anxiety and depressive disorders. Results: All patients scored above the cut-off points of 19 on the AKUADS. The mean score of study participants on AKUADS was 46 (range of possible scores from 0 to 75). There was no statistically significant difference between male and female study participants on AKUADS scores. Conclusions: The prevalence of depressive and anxiety disorders in patients with CKD is extremely high in the Pakistani population. The possible reasons for this high prevalence could be physical morbidities, lack of appropriate treatment facilities, financial burden, loss of bread winning roles as well as reduced quality of life associated with CKD.